2007
DOI: 10.1007/s10548-007-0032-3
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal Alterations of Brain Electrical Activity in Healthy Adults: A LORETA Study

Abstract: EEG background activity was investigated by low resolution brain electromagnetic tomography (LORETA) to test the diurnal alterations of brain electrical activity in healthy adults. Fourteen right-handed healthy male postgraduate medical students were examined four times (8 a.m., 2 p.m., 8 p.m. and next day 2 p.m.). LORETA was computed to localize generators of EEG frequency components. Comparing the EEG activity between 2 p.m. and 8 a.m., increased activity was seen (1) in theta band (6.5-8 Hz) in the left pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 50 publications
0
20
0
Order By: Relevance
“…EEGs were recorded between 8:00 and 10:00 in the morning (Toth et al 2007). A 22-ch EEG recording, using Ag/AgCl electrodes and two channels electro-oculogram (EOG) were continuously gathered for 2 min in the period of the experiment, respectively with the A.N.T.…”
Section: Eeg Recordingsmentioning
confidence: 99%
“…EEGs were recorded between 8:00 and 10:00 in the morning (Toth et al 2007). A 22-ch EEG recording, using Ag/AgCl electrodes and two channels electro-oculogram (EOG) were continuously gathered for 2 min in the period of the experiment, respectively with the A.N.T.…”
Section: Eeg Recordingsmentioning
confidence: 99%
“…Overall, the patients were treated and followed as usual. Healthy persons were recruited at the Department of Neurology, University of Pécs, under the approval of that Local Ethics Committee (Toth et al, 2007).…”
Section: Patients Healthy Control Persons and Methodsmentioning
confidence: 99%
“…In order to estimate the topographic distribution of theta activity in healthy persons, the 6.5 to 8 Hz averaged absolute (raw) LORETA results of 14 healthy persons were given. These data came from a prior study where they had not been explicitly published (Toth et al, 2007).…”
Section: Loreta Analysismentioning
confidence: 99%
“…There is reasonable evidence that resting-state power in the beta frequency band is weakest in the morning hours and that it increases during the late afternoon in healthy adults (Cacot et al, 1995; Gundel et al, 1983; Toth et al, 2007). There is also abundant evidence that motor performance is influenced by the biological clock (Carrier and Monk, 2000; Drust et al, 2005; Gueugneau and Papaxathis, 2010; Jasper et al, 2009), and a recent fMRI study of finger-tapping showed that time-of-day effects could be discerned in multiple motor regions (Peres et al, 2011).…”
Section: Introductionmentioning
confidence: 99%